Menelusuri Budaya Praktik Independensi Pengujian Audit pada Kantor Akuntan Publik - Afidah, Ridhatul; Mulawarman, Aji Dedi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to trace the culture of auditors’ financial report audit testing independence of Hari Purnomo and Jaswadi (HJA) Public Accounting Firm, Malang, utilizing an ethnomethodology approach. The results of this study revealed that the auditors of HJA Public Accounting Firm applied independence through three unique Javanese cultural behaviors: “manut (obedient), tatag (resilient), and not easily lured. “Manut” refers to complying with the rules, standards, and Code of Ethics as the guidelines in audit testing. Auditors also set boundaries in their relationship with clients, strengthen themselves by being “tatag” when dealing with the audit process with related parties, and are not tempted by any kind of “lure”. Abstrak Studi ini bertujuan untuk menelusuri budaya praktik independensi auditor dalam pengujian audit laporan keuangan di Kantor Akuntan Publik. Etnometodologi digunakan sebagai metode untuk menelusuri praktik independensi khususnya dalam pengujian audit yang dilakukan oleh KAP HJA, Malang. Hasil penelitian menunjukkan bahwa auditor di KAP HJA mempraktikkan independensi dengan tiga laku budaya Jawa yang unik, yaitu